'GA JT141‐14E45': A new soft red winter wheat cultivar adapted to Georgia and the U.S. Southeast region. Issue 3 (4th August 2021) - Mergoum, Mohamed; Johnson, Jerry W.; Buck, James W.; Sutton, Steve; Lopez, Benjamin; Bland, Daniel; Chen, Z.; Buntin, G. D.; Mailhot, Daniel J.; Babar, Md A.; Mason, Richard E.; Harrison, Stephen A.; et al.
Abstract: In Georgia and the southeast region of the United States, acreage of soft red winter wheat (SRWW) ( Triticum aestivum L.) has decreased in recent years. There is an urgent need to release new cultivars with high yield potential, resistance to yield‐limiting diseases and insects, and good baking quality to maximize value in regional markets. To address this, the SRWW breeding program at the University of Georgia (UGA), in collaboration with the SUNGRAINS breeding programs, developed 'GA JT141‐14E45' (Reg. no. CV‐1183, PI 689519), a SRWW cultivar released by the UGA College of Agricultural and Environmental Sciences and licensed to AGSouth (AGS) Genetics as AGS 3030. GA JT141‐14E45 is widely adapted to the U.S. Southeast, having high yield, good resistance to diseases such as leaf rust, stripe rust, powdery mildew, and Soil‐borne wheat mosaic virus (SBWMV) and to current biotypes of Hessian fly ( Mayetiola destructor Say). It has good resistance to Fusarium head blight (FHB) or scab. GA JT141‐14E45 has good grain volume weight and acceptable milling and baking quality. GA JT141‐14E45 was derived from the cross of 'AGS 2026'/'Jamestown'. Jamestown was used in the cross mainly for its resistance to FHB (FHB QTL 1A‐Neuse and 1B‐Jamestown). AGS 2026 is a UGA cultivar released in 2007 with very good disease resistance to rusts ( Yr17 / Lr37/Sr38 ), Hessian fly resistance ( H13 ), and excellent yield.